Darajat Imtilāk Ṭullāb Kulliyyat Dirāsāt al-Lughāt al-Raʾīsiyyah li Mahārāt al-Taʿallum al-Iliktrūnī al-Mutaʿalliqah bi al-Mūdil wa Fuṣūl al-Lughah al-ʿArabiyyah al-Iftirāḍiyyah - Nur Hamimi Zainuddin (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
The present study aims to identify the degree to which students of the Faculty of Major Language Studies at the Islamic Science University of Malaysia possess e-learning skills related to Moodle and Virtual Arabic Language Classrooms. The study was conducted on a sample of 183 students, consisting of 78 male and 105 female students. The research instrument consisted of two domains: skills related to Moodle and skills related to Virtual Arabic Language Classrooms. The findings revealed that all questionnaire items represented good levels of e-learning skills among the students of the Faculty of Major Language Studies at the Islamic Science University of Malaysia. The overall level of skill mastery was high, and the students' responses indicated a high degree of competence. The researcher attributes these findings to the general perception among the students that both Moodle and Virtual Arabic Language Classrooms effectively support the teaching and learning of the Arabic language. The results also confirm the importance of these learning platforms in creating positive learning experiences while encouraging and motivating students to support one another throughout the learning process.